Pemberdayaan Petani Singkong Desa Kendel, Kecamatan Kemusu, Kabupaten Boyolali melalui Sentuhan Fortifikasi-Fermentasi Singkong - Sri Hartini; Yohanes Martono (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2015)
Kendel village located in the Kemusu District, Boyolali. Cassava is one of the agricultural products in the region with 2.110 tons harvested cassava to the breadth of 212.4133 ha per year. Cassava plants is favorite plants for the population because it is relatively easy to cultivate and as a management area strategy because of limited water availability on the hilly areas. Up to now, post harvest processing of cassava is still using conventional methods and on sale in the form of raw cassava with its peels, and gaplek (dried cassava). While the cooked one are also served with simple ways, such as boiled cassava, fried cassava, roasted cassava, and lemet cassava. One of the constraints on the creation of cassava processing is limited diversification knowledge of the society Kendel as well as people do not yet understand the fortification of cassava. Close cooperation between Satya Wacana Christian University, Trukajaya Foundation, and Cassava Farmers Group realized empowerment, sortification, post harvest, advanced products, and increasing on economic value. The collabor ation was empowering community by using of participatory rural appraisal (PRA) method. Training have been done on post harvest handling, fortified cassava flour (mocaf), the manufacture of various products of mocaf flour, marketing training for products, monitoring and evaluation of processed products, and networking with other partners to develop programs based on local wisdom potential and organic as well. Various products have been produced from cassava flour fortified, processed products such as brownies, banana cake, cupcake, or cookies. Mocaf fortified flour sales price was Rp 8.000/kg.